Head and Neck Reconstruction with Chimeric Anterolateral Thigh Free Flap: Indications, Outcomes, and Technical Considerations. (24th September 2015) - Lawson, Bradley R.; Moreno, Mauricio A.
Abstract : Objective: Chimeric anterolateral thigh free flaps are composed of multiple skin paddles or muscular components that allow for the reconstruction of complex 3‐dimensional defects. We present our experience with the technique and applications for various head and neck defects. Study Design: Retrospective chart review. Setting: Academic tertiary care center. Subjects and Methods: Subjects include 24 consecutive patients undergoing reconstruction with a chimeric anterolateral thigh free flap by a single surgeon. Our algorithm for pharyngeal reconstruction with this technique is described. Data include demographics, indications, comorbidities, operative findings, and surgical outcomes. Results: The most frequent defects were pharyngocutaneous (n = 12, 50%) and skull base (n = 6, 25%). The flap consisted of a double skin paddle in 11 cases (45.3%) and a skin paddle with an independent component of vastus lateralis muscle in 13 cases (54.7%). Revision surgery was required in 4 cases and was associated with malnutrition ( P =. 022). There were no total flap losses, but partial loss (distal skin paddle in all the cases) was observed in 3 patients and was related to severe congestive heart failure ( P =. 021) and malnutrition ( P =. 021). All except 1 patient who underwent pharyngeal reconstruction resumed oral diet and achieved alaryngeal speech. Conclusion: Chimeric anterolateral thigh free flaps represent an excellent option for reconstruction of complex head and neck defects. Modifications to the technique are proposed in patients at high risk of surgical complications.